Behind the door : the dark truths and untold stories of the Cecil Hotel - Price, Amy (William Morrow, an imprint of HarperCollins Publishers, 2023)
When Amy Price took a temporary design job at an Art Deco hotel in Los Angeles to help a friend, she had no idea the path it would lead her down. Before long, she would become manager of the Cecil Hotel, seeking to make it more welcoming and correct its notoriety, not helped by sitting at the foot of Skid Row, or the fact that since its opening in 1927, there had been any number of deaths by suicide, and residents such as serial killers Richard Ramirez and Jack Unterweger. She cared about guests and residents alike, though she faced challenges on many fronts, with over eighty people dying during her decade of service. Among them was Elisa Lam, whose tragic death became the subject of a Netflix documentary series that captivated millions and led to its own controversies and unwarranted personal attacks on Amy. For the first time, Amy delves into her experiences at the Cecil Hotel. Equal parts memoir, true-crime, and cultural history, Behind the Door is essential to understanding one of America's most enigmatic hotels. --Amazon